DESIGN CRITERIAS OF PERFORMANCE BUILDING WITH GOOD SPATIAL QUALITY IN BANYUWANGI - Pratiwi, Intan Agustina; Dinapradipta, Asri; Noerwasito, Vicentius Totok (Border: Jurnal Arsitektur, 2023)
Fashion shows and music concerts held in Banyuwangi have different requirements and needs. So that the design criteria of one performance building with another are of course different because it adapts the requirements and needs of the event being held. Meanwhile, a performance building needs to have good spatial quality in order to meet the needs and requirements, as well as create comfort for its users. This study aims to explore the design criteria for performance building that can produce good spatial quality. The research method used is qualitative method based on primary data through field studies, and secondary data through literature studies. The results of the research are the formulation of performance building design criteria that can respond to the needs and requirements of fashion shows and music concerts in Banyuwangi. Exploration of performance building design criteria focuses on visual and acoustic aspects. So that the resulting criteria can be used as a reference for designing an effective and efficient performance building in meeting the various needs and requirements of the event, as well as creating comfort for its users.